A narrative review of long-term inorganic iodine monotherapy for Graves’ disease with a historical relationship between iodine and thyroid - Natsuko Watanabe (Endocrine Journal)
Almost a century has passed since Plummer reported the efficacy of short-term preoperative inorganic iodine therapy for Graves’ disease in the 1920s. Since there were concerns about the escape phenomenon and exacerbation with inorganic iodine, antithyroid drugs became the mainstay of pharmacotherapy for Graves’ disease following their development in the 1940s. With regard to long-term inorganic iodine monotherapy, Trousseau reported a case in the 1860s, and several subsequent reports suggested its efficacy. Around 1930, Thompson et al. published a number of papers and concluded that long-term inorganic iodine monotherapy was useful if limited to mild cases under careful follow-up. From Japan, in 1970, Nagataki et al. reported that, of 12 patients treated with inorganic iodine, three remained eumetabolic for more than two years. Since 2014, some reports have also been published from Japan. A summary of these recent reports is given below. The starting dose of potassium iodide is around 50 mg/day, and candidate responders have mild disease, with FT4 <2.76 ng/dL (35.5 pmol/L), a small goiter, and are female and elderly. Response rates are relatively high, at 60–80%, and the remission rate is about 40%. In cases of insufficient response, changing therapy should be considered. Inorganic iodine can be used as a possible alternative if the patient experiences adverse events with antithyroid drugs and/or prefers conservative treatments, with an understanding of their efficacy and limitations. These recent reports have been published from Japan, where iodine is sufficient, and the dose of inorganic iodine is empirical and requires further study.